Estimating the yield of a collector well with parallel infiltration galleries as laterals - Macuha, Richmark (Philippine Engineering Journal [eJournal])
In recent years, collector well with horizontal laterals is being used more often to tap groundwater resources. However, at the moment, majority if not all yield studies are focused on collector wells with radial orientation of laterals. In countries where trenchless technology is still uncommon, like in the Philippines, collector wells either have a single long lateral or parallel laterals. This paper presents applicable yield estimation techniques for collector wells with parallel laterals in the riverbed. The first method uses a source-sink pair model and image well theory, obtaining an approximate analytical solution. The second makes use of MODFLOW, a numerical approach to come up with a local groundwater model. The estimates from both are found to be in good agreement with actual yields measured in a study area. The developed equations can be used for rapid estimation of yield to other candidate sites. Although the MODFLOW model produced more accurate results than the approximate analytical method, it should also be used with caution as the estimates are usually greater than the actual, which can pose a problem for water supply development.